Pengaruh Motivasi Belajar Terhadap Prestasi Belajar IPA Siswa Kelas Atas Sdnegeri 1 Taruban Nogosari Boyolali Tahun Pelajaran 2015/2016 - Yuni Handayani, Dhayinta (2016)
The purpose of this research is to want to know whether there is a positive and significant controlling influence between motivation to learn against the achievements of learning science class students of SD Negeri 1 Taruban dan Nogosari Boyolali years 2015/2016 lessons. The population in this research is the whole class students of SD Negeri 1 Taruban dan Nogosari Boyolali years 2015/2016 lessons the students in grade 4 and grade 5 were 46 students. Samples used in research 30 students. The way the sampling used is simple random sampling with how randomized or elected sampel have. The hypothesis in this research is that there is a positive correlation between motivation to learn against the achievements of learning science SD Negeri 1 Taruban dan Nogosari Boyolali years 2015/2016 lessons. This research uses the method . Data collection techniques used is the method of observation, questionnaires and documentation. Questionnaires used to obtain data about the motivation of student learning. Data Analysis Techniques in this research using the T Test From the analysis of the data obtained in the analysis of the data for simple regression. The variables X (Learning) motivation with learning achievement (Y) , obtained the results of Prob. t 0,022 < 0.05. So H0 rejected, so that motivation to learn affects significantly and positively to the achievement of learning science. Thus the hypothesis "There Is the influence of motivation to learn on the outcome of the learning science class students of SD Negeri 1 Taruban dan Nogosari Boyolali lessons the year 2015/2016", Ho rejected". So it can be concluded the better motivation is owned by the students both from the internal factors and external factors students then the better nor the value of the results of the learning science students. Instead, when there is no motivation that comes from the internal and external factors students during the learning process and the value of achievement in learning science students will not increase